Approaches to integration of knowledge: a study of Al-Ghazali and Alwani’s views = Pendekatan ke arah mengintegrasikan ilmu pengetahuan: satu kajian terhadap pandangan Al-Ghazali dan Alwani - Gilani, Sayyid Muhammad Yunus; Islam, Tazul (IIUM Press, International Islamic University Malaysia, 2018)
This research aims to study the approaches to integrating scientific and Islamic knowledge based on the views of two selected Muslim scholar, namely Al-Ghazali and Alwani. A considerable amount of research has been produced on knowledge integration, yet there is still a lack of study in exploring the ‘processes’ of integration. Hence, this research highlights this particular aspect from both traditional and contemporary perspectives. Qualitative in nature, the data for this work was collected from the writings of the selected scholars and analyzed in order to find out how the integration is achieved. As a result, this study finds out two distinctive approaches to integration: Firstly, in al-Ghazali’s view, integration is an external and complementary factor where Islamic knowledge and science maintain their own entity but the later complements the former as a supportive tool; secondly, Alwani sees the integration as an internal and essential matter where a knowledge evolves as a result of a mix of scientific reading of the Quranic texts as well as reading of the nature based on Quranic worldview. ******************************************************** Kajian ini bertujuan mengkaji pendekatan untuk mengintegrasikan ilmu Sains dan Islam berdasarkan pandangan dua cendiakawan Islam iaitu Al-Ghazali dan Alwani. Sejumlah besar kajian telah pun dilakukan namun masih terdapat kekurangan kajian dari aspek proses integrasi ilmu pengetahuan. Oleh itu kajian ini secara khususnya akan memaparkan proses tersebut berdasarkan perspektif tradisional dan kontemporari. Disebabkan bersifat kualitatif, data-data kajian ini diperolehi daripada penulisan-penulisan para cendiakawan yang terpilih yang kemudiannya akan dianalisa untuk mengetahui proses bagaimana integrasi dapat dicapai. Hasil kajian mendapati dua pendekatan untuk tujuan integrasi, yang pertama menurut pandangan al-Ghazali, integrasi merupakan faktor luaran dan pelengkap dimana ilmu pengetahuan Islam dan Sains mengekalkan entiti tersendiri, namun Sains merupakan penyokong kepada ilmu pengetahuan tersebut. Kedua, Alwani melihat integrasi sebagai faktor dalaman yang penting untuk perkembangan ilmu hasil daripada pembacaan saintifik teks-teks al-Quran dan alam menurut perspektif al-Quran.